Development of a Conghua Cat Head Lion Dance Animation as a Catalyst for Intangible Cultural Heritage Preservation - Fei, Deng; Wong, Shaw-Chiang (Universitas Negeri Semarang, 2024)
Conghua Cat Head Lion Dance (CHLD) is a traditional dance art that faces challenges in inheritance and education. Animation is engaging and emotionally resonant, naturally appealing to the younger generation, making it a tool that scholars recommend for the preservation of intangible cultural heritage (ICH). This study employs animation as a catalyst to promote and preserve the art of CHLD among the younger Chinese generation by raising their awareness of it. This study was divided into three stages. In the first stage, a field investigation was conducted at the ancestral hall in Guangdong Province, China. Additionally, semi-structured interviews were held with four purposively selected inheritors to collect qualitative data. The application of thematic analysis revealed four distinctive elements that could be incorporated into the animation: (1) characters, (2) patterns and costumes, (3) props, and (4) performance techniques. In the second stage, an animation was created by incorporating CHLD elements, following The Cognitive Theory of Multimedia Learning (Mayer & Moreno, 1999) and The Animation and Design Principles for Instructional Animation (Betrancourt, 2005). In the third stage, a self-administered survey questionnaire was used to examine whether the CHLD animation had the potential to increase the awareness of CHLD culture preservation among a randomly selected group of 181 students from Guangzhou City Construction College and Guangdong Polytechnic. More than 75% of the respondents expressed positive views of the created CHLD animation. The study’s findings and the created animation reaffirmed the effectiveness of using digital media to preserve and promote CHLD culture, especially among China’s younger generation. This also offers a valuable reference for similar studies contributing to the sustainable development of ICH in the Chinese context.